2018
DOI: 10.2147/tcrm.s157603
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood stem cells transplantation as an adjunctive treatment strategy for liver cirrhosis in Chinese population: a meta-analysis of effectiveness and safety

Abstract: ObjectiveThe aim of the study was to evaluate the efficacy and safety of umbilical cord blood stem cells (USCs) transplantation combined with routine supportive therapy (RST) for liver cirrhosis (LC).Materials and methodsClinical trials involved in this research were searched from Web of Science, PubMed, EMBASE, Cochrane Library, Wanfang and CNKI database. Treatment effects, quality of life (QoL), adverse events and other outcome measures were extracted and evaluated.ResultsA total of 10 trials including 616 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Due to the intrinsic regenerative potential and immunomodulatory abilities, the stem cells (SCs) therapy has opened up a breakthrough approach to cure autoimmune disease. Meta-analyses of studies on SCs therapy indicated a certain potential to treat liver cirrhosis [3][4][5], chronic liver disease [6], inflammatory bowel disease [7] and ischemic heart disease [8]. SCs therapy also showed a potential effect to halt or abolish the autoimmune destruction of β cells and to generate functional β cells which could achieve optimized glycemic control in T1DM [9][10][11][12][13].…”
mentioning
confidence: 99%
“…Due to the intrinsic regenerative potential and immunomodulatory abilities, the stem cells (SCs) therapy has opened up a breakthrough approach to cure autoimmune disease. Meta-analyses of studies on SCs therapy indicated a certain potential to treat liver cirrhosis [3][4][5], chronic liver disease [6], inflammatory bowel disease [7] and ischemic heart disease [8]. SCs therapy also showed a potential effect to halt or abolish the autoimmune destruction of β cells and to generate functional β cells which could achieve optimized glycemic control in T1DM [9][10][11][12][13].…”
mentioning
confidence: 99%
“…14 Prior studies have shown that HUCB-MSCs can safely and effectively improve liver function as shown by improvements to Child-Turcotte-Pugh (CTP) and model for endstage liver disease (MELD) scores in patients with liver cirrhosis. 15,16 However, there is a lack of data on the long-term efficacy of umbilical cord mesenchymal stem cell transplantation, particularly in patients with liver cirrhosis. Moreover, transplantation of stem cells also carries safety risks such as the potential for tumor development.…”
Section: Introductionmentioning
confidence: 99%